Efektivitas Prone Position Sebagai Penatalaksanaan Hypoxemia Pada Pasien Covid-19 - Marini, Gita; Wibowo, Nugroho Ari; Salsabila, Shofwa (Indonesian Academia Health Sciences Journal, 2021)
Objective: To analyze a comprehensive summary of the article on the Effectiveness of the Prone Position as the Management of Hypoxemia in Covid-19 patients . Methods: Literature review of the journal Effectiveness of the Prone Position as the management of Hypoxemia in Covid-19 patients. Search articles via the internet with databases: Proquest, PubMed, Science Direct. With Population Covid-19, Intervention Prone Position, Outcome Management Hypoxemia. The review was carried out by 10 articles starting from 2019-2020, the full English text was then synthesized using a literature review table. Results: The effectiveness of prone position in patients with mild to moderate hypoxemia is recommended to do prone position by maintaining the position for 3 hours a day. Prone position can be done gradually with 2 hours in the morning, 2 hours in the afternoon, and 6 hours at night, with a total prone position time of 10–14 hours / day, taking into account the patient's tolerance or condition. Prone position is carried out in conjunction with other treatment measures, and does not affect the implementation of other treatments Conclusion: The Covid-19 emergency makes the need for oxygenation very important to overcome hypoxemia so that oxygen demand increases along with the increase in Covid-19 patients, with the prone position this can help minimize oxygenation needs in Covid-19 patients.